APEX University Research Agenda (AURA) Project (2008-2014): A USM initiative. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)

(untitled)
Universiti Sains Malaysia (USM) became the first institution of higher learning to be inducted in Malaysia’s Accelerated Programme for Excellence (APEX) in early September 2008 (Simrit and Chapman, 2008). With APEX the Ministry of Higher Education (MoHE) is expecting USM to be in the world’s top 100 universities by 2013, and among the elite 50 by 2020.